Peptide methionine sulfoxide reductase contributes to the maintenance of adhesins in three major pathogens. - Wizemann, T M (1996)
Pathogenic bacteria rely on adhesins to bind to host tissues. Therefore, the maintenance of the functional properties of these extracellular macromolecules is essential for the pathogenicity of these microorganisms. We report that peptide methionine sulfoxide reductase (MsrA), a repair enzyme, contributes to the maintenance of adhesins in Streptococcus pneumoniae, Neisseria gonorrhoeae, and Escherichia coli. A screen of a library of pneumococcal mutants for loss of adherence uncovered a MsrA mutant with 75% reduced binding to GalNAcbeta1-4Gal containing eukaryotic cell receptors that are present on type II lung cells and vascular endothelial cells. Subsequently, it was shown that an E. coli msrA mutant displayed decreased type I fimbriae-mediated, mannose-dependent, agglutination of erythrocytes. Previous work [Taha, M. K., So, M., Seifert, H. S., Billyard, E. & Marchal, C. (1988) EMBO J. 7, 4367-4378] has shown that mutants with defects in the pilA-pilB locus from N. gonorrhoeae were altered in their production of type IV pili. We show that pneumococcal MsrA and gonococcal PilB expressed in E. coli have MsrA activity. Together these data suggest that MsrA is required for the proper expression or maintenance of functional adhesins on the surfaces of these three major pathogenic bacteria.